Associação entre o status de vitamina D e síndrome metabólica e seus componentes em mulheres - Battaglia, Renata Giovannetti Costa (2017)
Recent studies have reported an association between vitamin D status and metabolic syndrome (MS) and its components. In relation to the female population, it is known that the prevalence of this syndrome increases during the menopause. However, studies evaluating the prevalence of MS and its association with serum vitamin D levels in postmenopausal women are still scarce. The present study aimed to analyze the association between vitamin D and MS and their components in pre and post menopausal women. This was an observational, cross-sectional and retrospective study aimed to analyze the association between vitamin D and MS, as well as its components, in pre- and postmenopausal women. It was performed with a sample of 516 women attended in two cardiology services between 2010 and 2014 in northern Paraná. The variables used were characteristics of physical examination, such as blood pressure and abdominal circumference; biochemical tests such as vitamin D, fasting glycemia, triglycerides and HDL cholesterol; in addition to the presence of systemic arterial hypertension (SAH) and type 2 diabetes mellitus (DM2). The patients were characterized in relation to the vitamin D status (adequate, insufficient or deficient), presence or not of the metabolic syndrome and menopause. Patients with the syndrome showed a higher prevalence of vitamin D deficiency (p=0.0007), arterial hypertension (p=0.0001), fasting glycemia (p=0.0037), low HDL (p=0.0017) and elevated triglycerides (p=0.0030). When comparing the menopausal and nonmenopausal women, the prevalence of hypovitaminosis D was higher in the second group. Menopausal women with metabolic syndrome had a higher prevalence of hypovitaminosis D (p = 0.0016). However, the causality between vitamin D status and the prevalence of MS still needs to be investigated and thus longitudinal studies evaluating the consequences of vitamin D supplementation on the components of MS are needed.